Neuroplasticity-based novel brain stimulation support intervention options for autistic population - Desarkar, Pushpal (Frontiers in Human Neuroscience, 2025)
Transcranial magnetic stimulation (TMS), introduced in 1985, has become a vital tool for investigating brain-behaviour relationships and therapeutic interventions. Repetitive TMS (rTMS) as a therapeutic tool has shown promise for various neuropsychiatric conditions, including autism, which affects approximately 1% of the global population. Evidence suggests that atypical neuroplasticity characterizes the neurobiology of autism. Recent studies using TMS paradigms like theta-burst stimulation (TBS) indicate an excessive neuroplasticity or hyper-plasticity in the form of an excessive long-term potentiation (LTP) in the motor cortex of autistic adults compared to neurotypical controls. Hyper-plasticity may negatively impact cognitive and behavioural outcomes. Our proposed neuroplasticity-based rTMS intervention protocols aim to address motor function, sensory sensitivities, and executive function difficulties in autistic adults. We present a testable framework to evaluate neuroplasticity in the motor, sensory, and dorsolateral prefrontal cortices, hypothesizing the presence of hyper-plasticity in autistic adults. We anticipate that this hyper-plasticity underpins motor, sensory, and executive function difficulties in autistic adults. Additionally, we propose investigating the efficacy of bilateral rTMS to reduce hyper-plasticity and improve these functions in autistic adults. This approach not only seeks to enhance therapeutic options but also provides biological insights into the brain mechanisms underlying some of the common autism-associated difficulties.